Kombinasi Terapi Bubuk Bayam Merah (Amaranthus Tricolor) dan Minyak Ikan Tuna Untuk Penanganan Balita Stunting - Satiti, Ika Arum Dewi; Wahyuningrum, Ari Damayanti (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Stunting is a national level health problem experienced by the majority of Indonesian toddlers. Stunting has a negative impact on human resources in the future, both physically and intellectually. The problem of stunting is caused by multiple factors, one of which is poor fulfillment of the nutritional needs of toddlers. The combination of fulfilling macro and micro nutrition in stunted toddlers is an effort needed to treat stunted toddlers. To determine the effectiveness of combination therapy of red spinach powder and tuna fish oil for treating stunted toddlers. The method used in this research was a quasi-experiment with a randomized pretest-posttest control group design. The results of measuring nutritional status in stunted toddlers were analyzed using the independent T - test. Combination therapy was given to 52 stunted toddlers who were divided into 2 groups, namely control and treatment groups. Combination therapy consists of providing high macronutrient nutrition (tuna fish oil) as the main food and providing high micronutrient nutrition (red spinach powder) as a snack. The results of this study prove that there were significant changes in nutritional status in the treatment group. The average weight of toddlers before giving combination therapy was (10.885) and after giving BB (11.855) with a P value of 0.000. Meanwhile, the results of the analysis of the difference in mean weight between the treatment group and the control group were found to be significantly different with a difference of 1.98 and a P value of 0.035. Nutritional intervention (a combination of red spinach powder and tuna fish oil) is effective in increasing the weight of toddlers with stunting Keywords: Stunting, Red Spinach, Tuna Fish Oil, Toddlers  ABSTRAK Kondisi stunting merupakan masalah kesehatan tingkat nasional yang dialami oleh sebagian besar balita Indonesia. Stunting menyebabkan efek jangka pandang di masa mendatang yakni buruknya kualitas sumber daya manusia baik dari fisik maupun kognitif. Masalah stunting disebabkan oleh multi factor salah satunya adalah buruknya pemenuhan kebutuhan nutrisi balita. Kombinasi pemenuhan gizi makro dan mikro pada balita stunting merupakan upaya yang dibutuhkan dalam penanganan balita stunting. Mengetahui efektifitas terapi kombinasi bubuk bayam merah dan minyak ikan tuna untuk penanganan balita stuting. Penelitian ini menerapkan metode eksperimen semu (quasi-experiment) dengan rancangan randomized pretest-posttest control group design. Hasil pengukuran status gizi pada balita stunting di analisa menggunakan uji T tidak berpasangan. Terapi kombinasi diberikan kepada 52 Balita stunting yang dipecah menjadi 2 kelompok, yakni kelompok kontrol dan perlakuan. Terapi kombinasi terdiri dari pemberian nutrisi tinggi makronutrien (minyak ikan tuna) sebagai makanan utama dan pemberian nutrisi tinggi micronutrient (bubuk bayam merah) sebagai makanan selingan. Data perubahan status gizi berupa peningkatan rerata BB/U signifikan pada kelompok perlakuan. Rerata status gizi BB/U balita sebelum pemberian terapi kombinasi (10,885) dan setelah pemberian BB/U (11,855) dengan P value 0.000. Kemudian hasil perbedaan rerata status gizi BB/U kelompok control didapatkan beda signifikan dengan selisih 1,98 dan P value 0,035. intervensi nutrisi (kombinasi bubuk bayam merah dan minyak ikan tuna) efektif dalam meningkatkan BB balita dengan stunting Kata Kunci: Stunting, Bayam Merah, Minyak Ikan Tuna, Balita